2013
DOI: 10.1093/jac/dkt504
|View full text |Cite
|
Sign up to set email alerts
|

Extended-spectrum  -lactamase- and AmpC  -lactamase-producing D-tartrate-positive Salmonella enterica serovar Paratyphi B from broilers and human patients in Belgium, 2008-10

Abstract: This study showed that the clonal population of multidrug-resistant serovar Paratyphi B dT+, persisting in broilers in Belgium for the last decade, recently acquired various plasmid-borne ESC resistance determinants, constituting a major concern for public health. Further surveillance programmes and research are an absolute necessity to understand their epidemiology and to propose interventions to limit the spread of ESC- and multidrug-resistant Salmonella spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
3
20
0
1
Order By: Relevance
“…This kind of structure has been very common in South America (Andrade et al, 2010;Power et al, 2005;Quiroga et al, 2013), whereas, it has been also found sporadically in Spain (Valverde et al, 2006). Additionally, in a recent study in Belgium, similar class 1 integron structures were identified in Salmonella enterica isolated from poultry (Doublet et al, 2014). Thus, this study report for the first time the presence of bla CTX-M-2 genes harbored by complex class 1 integrons in Enterobacteriaceae strains recovered from retail chicken meat in Brazil.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This kind of structure has been very common in South America (Andrade et al, 2010;Power et al, 2005;Quiroga et al, 2013), whereas, it has been also found sporadically in Spain (Valverde et al, 2006). Additionally, in a recent study in Belgium, similar class 1 integron structures were identified in Salmonella enterica isolated from poultry (Doublet et al, 2014). Thus, this study report for the first time the presence of bla CTX-M-2 genes harbored by complex class 1 integrons in Enterobacteriaceae strains recovered from retail chicken meat in Brazil.…”
Section: Discussionsupporting
confidence: 64%
“…With regard to P. mirabilis strain S11, the genetic environment of bla CTX-M-2 is composed of a complex class 1 integron and an ISCR1-associated sequence, with dfrA1 and aadA1 gene cassettes located within the variable region, which confer resistance to trimethoprim and streptomycin, respectively. This arrangement of gene cassettes was found in E. coli and Salmonella isolated from poultry in Korea and in Belgium (Dessie et al, 2013;Doublet et al, 2014) and from clinical isolates from animals in Ireland (Karczmarczyk et al, 2011). K. pneumoniae S105 presented only the dfrA1 gene in the variable region, which has not been previously reported; and while E. coli S137 presented the dfrA7 gene, a variant of dfrA1 previously found in a E. coli from an unhealthy animal in Ireland (Karczmarczyk et al, 2011), E. coli Lac60 carried only the aadA1 gene in the variable region, such as In2::ISCR1::bla CTX-M-2 integron previously reported in Argentina (Quiroga et al, 2013).…”
Section: Discussionmentioning
confidence: 68%
“…In contrast, bla CTX-M-55 has mainly been reported from Asian enterobacterial isolates (58). Other bla CTX-M genes identified in this study were confined to a specific serotype, like bla CTX-M-2 to S. Paratyphi B (15) and bla CTX-M-9 to S. Typhimurium (Fig. 4).…”
Section: Resultsmentioning
confidence: 56%
“…In Europe, average resistance rates against ciprofloxacin (FQ) and cefotaxime (CSP) remain relatively low for S. enterica at Ͻ6% and Ͻ2%, respectively (1). However, a plethora of studies report high-level FQ and CSP resistance emerging in different parts of the world (11)(12)(13)(14)(15), and global travel and food trade increase the likelihood of acquiring infection from nondomestic sources. As such, it is crucial to closely monitor trends in resistance and the prevalence of mobile and nonmobile genetic determinants underlying resistance to these first-line drugs.…”
mentioning
confidence: 99%
“…Salmonella strains possessing this serotype remain a common cause of gastroenteritis, being responsible for recent outbreaks in the United Kingdom (10), Belgium (11), Scandinavia (12), Canada (13, 14), and the United States (15), as well as a cause of invasive disease around the world in travelers (16). Moreover, since the late 1990s, two different clones of S .…”
Section: Introductionmentioning
confidence: 99%